The efficacy of executive coaching interventions for succession management at local company X in Botswana - Sempe, Rosi (My University, 2020)
Local Company X is a multinational mining company based in Botswana that often employs expatriate workforce in order to execute its organisational objectives where skills are deemed not available in country. Localisation policy of the Government of Botswana has since made the importation of skills through expatriation a less preferred option. Local Company X has put in place a succession management process to develop high potential employees to succeed into senior roles, often held by expatriates. Executive coaching is an intervention provided to the successors to aid their development and accelerate their readiness levels to ascend to these senior roles. The purpose of this study was to establish how executive coaching intervention aids succession management and the consequent evaluation of executive coaching effectiveness. The study explored if the current coaching approach at local company X is aligned to the purpose of succession management by establishing (1) the coaching approaches used (2) how effective they are perceived to be for succession management lastly (3) how the effectiveness is evaluated. The research used a qualitative methodology and data was collected through semi-structured interviews from 11 respondents. A thematic analysis of all responses revealed that coaching was perceived to be effective through its employed coaching approach which allowed for flexibility in order to address the unique needs of coachees, which often changed during coaching. It was established that an effective coaching approach allows for the coachee to set the agenda while the coach subjects the agenda to a process without unnecessary structure or techniques that are ill-fitting for the purpose of coaching. Lastly, the finding that the HR office has no clear process to evaluate coaching effectiveness means that an unequivocal demonstration of coaching effectiveness remains elusive, despite rich anecdotal evidence this research has unearthed. Coaching has its place in building human capital in Botswana and this study demonstrated how executive coaching is an effective intervention for preparing a successor for succession and this has practical implications.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Business Executive Coaching submitted to the Faculty of Commerce, Law and Management, School of Business, University of the Witwatersrand, Johannesburg, 2020
Keywords: SDG-8: Decent work and economic growth